Indoor air quality in urban child care institution (nurseries & kindergarten): the characterization of particulate matter (PM) and its relation to airborne enteric microorganisms - Mohd Aris, Mohd Shukri; Chowdhury, Ahmed Jalal Khan; Yunus, Kamaruzzaman; Mohd. Din, Shamzani Affendy (2018)
Poor Indoor Air Quality known as 80% of the occupant had potential toward Sick Building Syndrome (SBS) that resulting in Building Related Illness (BRI) such as respiratory symptoms. Recently, respiratory symptoms among children cases increased dramatically are believed due to poor ventilation system design despite poor Indoor Air Quality (IAQ). Despite this poor health status, the study of IAQ in the child care institution was still limited. Due to these reasons, this study was conducted to see the relationship of airborne and biological pathogenic microorganism from children nasal swab analysis also to observe the prevalence of respiratory symptoms among children in selected child care institutions. This study was divided into three main objectives. The first one is an establishment of IAQ dataset in four childcare institutions with a correlation of three different microenvironments and four different background areas. The second objective is to identify the airborne pathogenic microorganism species and correlation with biological samples collected from children nasal. The third objective is the prevalence of respiratory health symptoms among children and correlation with a pathogenic microorganism from children nasal. The airborne microbial sampling was done by using Surface Air System Indoor Air Quality (SAS IAQ), a viable air sampler for IAQ assessment. The physical parameter will be measured by multiprobe anemometer to measure temperature, humidity, air velocity, air flow while for chemical analysis DustMate will be used to measure the concentration of particulate matter (PM) respectively. The sampling times were divided into four slots for 8 hours according to childcare schedule at the sampling point in three different microenvironments. The data obtained were compared with the established standard reference known as the Industrial Code of Practice on Indoor Air Quality (2010) constructed by the Department of Occupational Safety and Health (DOSH). Teachers and parents were randomly selected were invited to complete set of questionnaires by interview session that was adapted and slightly modified from Recommended Respiratory Disease Questionnaires for children by American Thoracic Society (ATS-DLD-78-C). Lastly, biological samples of children nasal were collected by nasal swab for culture sensitivity test for identification of microorganism. The data were analyzed by Statistical Package for Social Sciences (SPSS Version 23.0) and Microsoft Excel 2013. At the end of this study, it shows that most of the IAQ parameters such as temperature, humidity, and CFUm-3 for bacteria in the selected child care institutions were exceeding standard guideline by ICOP 2010. Moreover, there is the highly significant difference in IAQ parameters concentration in kindergarten station compare with a control station in term of occupancy factor. This study also identified similar species in indoor airborne microorganism and microorganism from children nasal swab analysis such as Staphylococcus aureus.spp. Bacillus and Pseudomonas aeruginosa.spp. This finding was also reflected to significant difference in term of the airborne pathogenic microorganism with respiratory symptoms among children in selected childcare institution.